Peran Kepala Sekolah dalam Menumbuhkan Nilai-nilai Spiritual Siswa di SDI Nurulhuda Jember - Rizal, Syaiful; Qiptiyah, Titin Mariatul (Al-Riwayah : Jurnal Kependidikan, 2021)
Education is a basic need that shapes the human mindset and personality. In this era of globalization, humans are not attacked through war, but through moral destruction. This is a consideration in educating and shaping the child's personality so as not to fall into values ​​that are not in accordance with the teachings of Islam. Cultivating spiritual values ​​becomes the basis for providing a foundation for children to fight against changing worlds. The research method used is descriptive qualitative research. Data collection is obtained from information, places and activities of school principals, and documents. Data collection techniques in the form of in-depth interviews, direct observation, and recording documents. The data validity test was carried out by applying source triangulation. Data analysis techniques are in the form of data condensation, data presentation, conclusion or verification. The results of the research are in the form of findings, namely the development of spiritual values ​​of students at SDI Nurulhuda Jember through learning in the classroom which is determined by activities that have been drafted and which have been carried out by the school.The principal emphasizes spiritual values ​​to be taught to students and to always carried out in school and outside of school, such as the things that are supervised in student learning are religious values, moral values, ethical values, and the true value of these four points which are the assessments of principals and teachers in fostering students' spiritual values ​​in classroom learning.